Investigation of platelet function and platelet disorders using flow cytometry. (2nd January 2016) - Rubak, Peter; Nissen, Peter H.; Kristensen, Steen D.; Hvas, Anne-Mette
Abstract: Patients with thrombocytopenia or platelet disorders are at risk of severe bleeding. We report the development and validation of flow cytometry assays to diagnose platelet disorders and to assess platelet function independently of platelet count. The assays were developed to measure glycoprotein levels (panel 1) and platelet function (panel 2) in sodium citrated blood. Twenty healthy volunteers and five patients diagnosed with different platelet disorders were included. Glycoprotein expression levels of the receptors Ia, Ib, IIb, IIIa and IX were measured and normalised with forward scatter (FS) as a measurement of platelet size. Platelet function was assessed by CD63, P-selectin and bound fibrinogen in response to arachidonic acid, adenosine diphosphate (ADP), collagen-related peptide, ristocetin and thrombin receptor-activation peptide-6. All patients except one with suspected δ-granule defect showed aberrant levels of glycoproteins in panel 1. Glanzmann's thrombasthenia and genetically verified Bernard–Soulier syndrome could be diagnosed using panel 1. All patients showed reduced platelet function according to at least one agonist. Using panel 2 it was possible to diagnose Bernard–Soulier syndrome, δ-granule defect and GPVI disorder. By combining the two assays, we were able to diagnose different platelet disorders and investigate platelet function independent of platelet count.